Exposição e proteção solar da população escolar: um Estudo de Caso aplicado na Região de Castanhal-PA - CARDOSO, Jaciani Campos (2022)
It is evident that it can cause frequent exposure to the sun's rays. In view of this, it is relevant to make the school population aware of the dangers exposed by exposure to UV rays. For this reason, the present work aimed to make the school population aware of the frequent exposure of these solar rays. A quantitative-employment of a municipality-PA case study was carried out, where the job-qualified the schools of the study-property. The creation of the Folder was extremely important to promote a work, as it served the best interest, as it is believed that this material is promoted by the school population.